Production System and Technology Adoption Profile of Black Pepper Cultivation in Kerala - Rejula, K; Lijo, T; Rajeev, P (Journal of Agricultural Extension Management, 2018)
Within India, Kerala is the spice garden. However, the pepper cultivationsystem in Kerala is now handicapped by a number of problems. The yield ofthis crop has declined mainly due to senile plantations and minimum inputuse, on account of declining market price and declining profit margin. Thepresent study was undertaken covering three districts of Kerala through asample survey to study the features of the production system and track majorshifts, study the technology adoption profile of the farmers and identify majorconstraints as perceived by the farmers. Around 38 per cent of the farmersadopted organic production system and technology adoption profile showed aless input intensive approach. Even though 60 per cent of farmers practicedrain fed cultivation, 15 per cent fully irrigated and 25 per cent adoptedirrigation partially. Majority of the farmers were holding land between 80cents to 4.5 acres. Around 40 per cent of the total vine population was inthe pre-bearing stage. There is slow and gradual increase in adoption rate ofimproved varieties and majority of the farmers sourced new planting materialfrom own fields, showing less dependence on public and private nurseries. Themajor field problems reported by the farmers are pre-bearing loss of the vines,and many biotic problems like pest and disease incidence and environmentalproblems like shifts in climate especially rainfall.